1999
DOI: 10.1176/jnp.11.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Persisting Insomnia Following Traumatic Brain Injury

Abstract: Persisting insomnia secondary to traumatic brain injury, rarely reported and documented, is described in an adult male following head injury. The neuronal mechanisms underlying this sleep disorder as well as the neuropsychological concomitants and therapeutic approaches are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Despite the widely accepted hypothesis that damage to the cerebral structures regulating sleep might result in sleep disturbance in TBI patients, no convincing neuroimaging evidence has been obtained. Some studies found no structural abnormalities on cerebral imaging (CT or MRI scans) despite significant sleep disturbance [33,34]. Others failed to illustrate relationship between location of injury on CT scan and presence of sleep disturbance [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widely accepted hypothesis that damage to the cerebral structures regulating sleep might result in sleep disturbance in TBI patients, no convincing neuroimaging evidence has been obtained. Some studies found no structural abnormalities on cerebral imaging (CT or MRI scans) despite significant sleep disturbance [33,34]. Others failed to illustrate relationship between location of injury on CT scan and presence of sleep disturbance [14].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, if FPI and secondary hypoxemia reduced the motivational value of food, then food intake would be reduced much less in the light than in the dark, which sustained the largest reductions in accuracy. A second explanation might be that rat's sleep in the light was more fragmented by FPI and secondary hypoxemia than by FPI alone (Tobe et al, 1999). As a consequence, rats in the FPI-hypoxia group were perhaps more likely to commit errors during the dark, which is the photoperiod during which rats were most actively executing the visual discrimination.…”
Section: Light/dark Cyclementioning
confidence: 99%
“…Reduced sleep efficiency 8 and increased sleep fragmentation post-TBI [9][10][11] have been reported. Some studies have shown increased sleep onset latency (SOL), 8,12 while others have reported no difference. 9,10,13 Findings regarding sleep architecture are also inconsistent, with studies reporting no changes in patients with TBI, 8 increased slow wave sleep, 11 reduced REM sleep, 11,13 increased REM in the second half of the night, 14 no change to REM, 8 or decreased REM onset latency.…”
mentioning
confidence: 99%
“…Several studies (some single case) report no structural abnormalities on cerebral imaging (MRI or CT) despite significant sleep disturbance. 12,17,38 Others have been unable to show associations between location of injury on CT or MRI scan with reports of sleep disturbance. 3 Our own study indicates that cerebral damage associated with TBI may disrupt the neural structures regulating sleep-wakefulness, including synthesis of melatonin by the pineal gland, which may not reliably be revealed with nonfunctional imaging.…”
mentioning
confidence: 99%